Elementary School Third Grade Students’ Expectations of Their Teachers in The Course of Language Education - Sabri Sidekli; Zeliha Cura; Alper Yorulmaz (International Journal of Evaluation and Research in Education (IJERE), 2018)
The purpose of the study is to determine the elementary school third grade students’ expectations of their classroom teachers within the context of the course of language education. The sampling of the study is comprised of 200 elementary school third grade students attending elementary schools in the Milas Province of the city of Muğla. The data were gathered by means of the questionnaire, which had six sub-categories, in order to identify students’ expectations of their teachers. The findings of the study revealed that the students have high expectations of their teachers in terms of the sub-dimensions of active participation, verbal participation, written participation, participating in reading, inclusion of the topics and measurement and evaluation. The students’ expectations of their teachers in relation to the sub-dimension of measurement and evaluation were found to be varying significantly depending on the gender variable. This difference is in favor of boys.